Consolidated financial reporting - Taylor, P. A (Paul Chapman, 1996)
Earlier edition had title: Consolidated financial statements; Includes bibliographical references and indexes; This book introduces and examines what is currently the most central and controversial area in financial reporting. It is designed so that readers with particular interests can easily find their way through clearly marked sections